Process Identification and Operational Efficiency Improvement in a Restaurant Chain : A Case Study of Cruz Group - Gavino, Emily (2025)
This bachelor’s thesis aims to explore operational inefficiencies in a growing restaurant chain, analyzing Cruz Group as a subject to improve its processes and enhance operational efficiency. The study's theoretical background focuses on restaurant operations and common problems as a start-up. It defines the use methodology frameworks DMAIC, SIPOC, Pareto, Lean, and Six Sigma. DMAIC is applied to the selected process of a restaurant with its proper definition for analysis. Data collected from real-time restaurant operations provide insights into the restaurant’s inefficiencies. Tools are used to improve workflows, optimize resource allocation, and improve customer satisfaction. Recommendations include adopting the lean tool (Mieruka) visual management to enhance critical-to-quality (CTQ) parameters. Ultimately, a control system is provided to have continuous and successful results.